2013
DOI: 10.1177/1053815113507111
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Accessing Services for Young Children

Abstract: This study investigates barriers to accessing services for children under age 3 presenting with language delays and behavioral difficulties, including language barriers for Spanish-speaking families. Using a telephone script, researchers called 30 agencies in Los Angeles County, including regional centers (the state network of Part C agencies for children with developmental disabilities), mental health centers, and schools, requesting services for a 2-year-old child. Outcomes of calls were compared by agency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Regarding this latter concern, readers may recall that 48.72% of respondents’ children were only in their first 6 months of EI service delivery. Despite the federal Child Find mandate for earlier screening and referral of more eligible children earlier in development, this aligns with pervasive national concern with delayed access to needed EI services, with younger eligible children in the birth to 3 age range more commonly receiving fewer EI services than older children (e.g., BLIND REVIEW; Elbaum, Celimli-Aksoy, Marshall, & Berkovits, 2017; McIntyre & Zemantic, 2017; Williams, Perrigo, Banda, Matic, & Goldfarb, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this latter concern, readers may recall that 48.72% of respondents’ children were only in their first 6 months of EI service delivery. Despite the federal Child Find mandate for earlier screening and referral of more eligible children earlier in development, this aligns with pervasive national concern with delayed access to needed EI services, with younger eligible children in the birth to 3 age range more commonly receiving fewer EI services than older children (e.g., BLIND REVIEW; Elbaum, Celimli-Aksoy, Marshall, & Berkovits, 2017; McIntyre & Zemantic, 2017; Williams, Perrigo, Banda, Matic, & Goldfarb, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, EI programs have been shown to be beneficial to children at increased risk of experiencing developmental delays and their families. However, research has revealed significant challenges in connecting children successfully with the program (Williams, Perrigo, Banda, Matic, & Goldfarb, 2013).…”
Section: Educational Significancementioning
confidence: 99%
“…Specifically, more research is needed to highlight the voices of those families who are not successfully connected with EI. More research is also needed investigating the EI referral experiences of more culturally and linguistically diverse families, as previous research has indicated that parents/caregivers who speak a language other than English have more difficulty connecting with EI (Williams et al, 2013). Well-conducted research exploring the experiences of families will ensure that the time, thought, and effort that goes into implementing widespread systems yields maximum benefit and reaches the most vulnerable children and families.…”
Section: Future Directionsmentioning
confidence: 99%
“…Children from the following backgrounds are more likely to have difficulty accessing services: (a) culturally and linguistically diverse (Feinberg et al, 2011; García & Ortiz, 2006; Harry, 2008; Williams et al, 2013;K. E. Zuckerman et al, 2013), (b) low socioeconomic status (SES; McManus et al, 2009; Williams et al, 2013), (c) rural settings (Grant & Isakson, 2013), and (d) uninsured (Shapiro & Derrington, 2004).…”
Section: Mismanagedmentioning
confidence: 99%